First Five - Year Plan for Tripura A Summary of the State Plan - Government of Tripura (Government of Tripura, 1953)
The First Five-Year Plan for Tripura marked a foundational effort to address the socio-economic challenges of a predominantly rural and agriculturally dependent state following its integration into the Indian Union in 1949. Characterized by hilly terrain, extensive forest cover, limited urbanization, and widespread poverty, Tripura required targeted developmental interventions to modernize its economy and improve living standards. The Plan emphasized strengthening public health infrastructure through the expansion of V. M. Hospital in Agartala, construction of new hospitals and dispensaries, and implementation of vaccination and preventive health programmes. Significant improvements in patient access demonstrated early success in healthcare delivery. Agricultural development formed the core of the Plan, focusing on improved seed distribution, land reclamation, minor irrigation, horticultural expansion, and gradual transition from shifting cultivation (Joom) to more sustainable farming practices. Given the limited proportion of land under cultivation, these initiatives aimed to enhance productivity and ensure food security. Forest management initiatives promoted afforestation and community participation in expanding forest cover. The Plan also encouraged cooperative development and the growth of cottage industries to diversify rural income sources. Establishment of industrial training institutes and marketing support mechanisms strengthened local craftsmanship and employment opportunities. With substantial financial allocations across agriculture, irrigation, roads, and social services, the Plan laid the groundwork for Tripura’s long-term socio-economic transformation. It represented a strategic move toward integrated rural development, infrastructure expansion, and sustainable resource management, setting the stage for continued progress in subsequent planning periods.
Government of India, Planning Commission
Government of India, Planning Commission
Keywords: State Plan; Tripura; Rural Development; Agricultural Modernization; Shifting Cultivation (Joom); Minor Irrigation; Public Health Infrastructure; Forest Management; Afforestation; Cooperative Movement; Cottage Industries; Socio-Economic Development